2011
DOI: 10.1007/s12204-011-1113-8
|View full text |Cite
|
Sign up to set email alerts
|

Explore the possibility of forming fcc high entropy alloys in equal-atomic systems CoFeMnNiM and CoFeMnNiSmM

Abstract: YE Guo-xin ( ) ZHANG Li-kun ( ), CHEN Tuo ( ), ZHANG Wen-jun ( ), ZHENG Zhen-huan ( ) Li Qiang ( ), SHAO Yan-qun ( ), ZHOU Bai-yang ( ), WANG Chen ( ) Abstract: The multi-principal high-entropy alloys (HEAs) are promising new alloys. However, it is a challenge to screen out the suitable composition from the diverse combinations. Referring to the prototype AuCu3 with AB3-L12 structure, where it becomes a face-centered cubic (fcc) structure if element A and B are the same element, the site occupying tendencies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The probability of the formation of fcc single-phase HEAs in the systems MnFeCoNiM and MnFeCoNiSmM (M -an other metallic element) based on a thermodynamic sublattice model and first-principles calculations was examined in [95]. This approach can give an idea whether particular elements prefer to be equally distributed on the Wyckoff positions or have a tendency to occupy only certain sites.…”
Section: Nominal Compositionmentioning
confidence: 99%
“…The probability of the formation of fcc single-phase HEAs in the systems MnFeCoNiM and MnFeCoNiSmM (M -an other metallic element) based on a thermodynamic sublattice model and first-principles calculations was examined in [95]. This approach can give an idea whether particular elements prefer to be equally distributed on the Wyckoff positions or have a tendency to occupy only certain sites.…”
Section: Nominal Compositionmentioning
confidence: 99%
“…Zhang and Zhou [37] determined necessary conditions on entropy of mixing, atomic size, and enthalpy of mixing needed to be in the high-entropy regime. More recently, Wang et al [38] studied the transformation from fcc to bcc based on atomic packing efficiency and lattice distortions and Zhang et al suggested how to downselect potential alloying additions to 4-and 5-element fcc-based HEA (CoFeMnNi + X and CoFeMnNiSm + X) based on first-principles calculations and site occupancy schemes [39].…”
Section: Introductionmentioning
confidence: 99%